2016
DOI: 10.5489/cuaj.3578
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the readability of patient information materials for common urological conditions

Abstract: Introduction: Health literacy has been shown to be an important determinant of outcomes in numerous disease states. In an effort to improve health literacy, the Canadian Urological Association (CUA) publishes freely accessible patient information materials (PIMs) on common urological conditions. We sought to evaluate the readability of the CUA's PIMs. Methods: All PIMs were accessed through the CUA website. The Flesch Reading Ease Score (FRES), the Flesch-Kincaid Grade Level (FKGL), and the number of education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 12 publications
4
22
0
1
Order By: Relevance
“…Consistent with the results of previous English and German PEM readability assessments [11][12][13]16], only 13.8% (12/87 assessments; Table. 2) met the NIH readability recommendations of a 7th-8th grade reading level [15].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with the results of previous English and German PEM readability assessments [11][12][13]16], only 13.8% (12/87 assessments; Table. 2) met the NIH readability recommendations of a 7th-8th grade reading level [15].…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that despite complex medical content, the readability of PEMs can be significantly improved by using simpler sentences and shorter words. Dalziel et al [12] reported on an average grade level improvement of 3.1 in PEM comprehension by simple substitution of multisyllabic words, with a further reduction by simplification of sentence structure [25,26]. These simple measures are easily applicable to German PEMs and might help to improve their readability significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Although limited data exist regarding the sources of information that pediatric patients with SCD and their families use to inform their decision-making surrounding medication acceptance, previous studies have found a positive association between accurate patient education about therapy and adherence. 15,21 Written information materials in particular have been shown to contribute to patient decision-making regarding therapy initiation in several other disease states [22][23][24] and serve as an influential adjunct to patient counseling. Therefore, the goal of this study was to evaluate the written material provided to patients with SCD by pharmacies to gain a better understanding of the information available to patients and to compare this information to a reference standard HU patient information handout (PIH) for patients with SCD.…”
mentioning
confidence: 99%
“…1 Like many of my physician colleagues, I wrote patient information handouts on various topics to reinforce and supplement my verbal description presented at the office or the hospital. In June 1998, at the CUA Annual Meeting in Halifax, NS, I suggested to my mentor and then CUA President-Elect, Denis Hosking, that this was a project that the CUA could take on as a benefit to the membership.With its resources, the CUA could develop a product with improved graphic and text content and establish the required infrastructure for efficient distribution of printed patient information materials to urologists, who could hand them out to their patients.…”
mentioning
confidence: 99%